SARS-CoV-2: Structure, Biology, and Structure-Based Therapeutics Development - Wang, Mei-Yue; Zhao, Rong; Gao, Li-Juan; Gao, Xue-Fei; Wang, De-Ping; Cao, Ji-Min (Frontiers in Cellular and Infection Microbiology, 2020)
The pandemic of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been posing great threats to the world in many aspects. Effective therapeutic and preventive approaches including drugs and vaccines are still unavailable although they are in development. Comprehensive understandings on the life logic of SARS-CoV-2 and the interaction of the virus with hosts are fundamentally important in the fight against SARS-CoV-2. In this review, we briefly summarized the current advances in SARS-CoV-2 research, including the epidemic situation and epidemiological characteristics of the caused disease COVID-19. We further discussed the biology of SARS-CoV-2, including the origin, evolution, and receptor recognition mechanism of SARS-CoV-2. And particularly, we introduced the protein structures of SARS-CoV-2 and structure-based therapeutics development including antibodies, antiviral compounds, and vaccines, and indicated the limitations and perspectives of SARS-CoV-2 research. We wish the information provided by this review may be helpful to the global battle against SARS-CoV-2 infection.